Orphan SelD proteins and selenium-dependent molybdenum hydroxylases - Haft, Daniel H (BioMed Central, 2008)
Bacterial and Archaeal cells use selenium structurally in selenouridine-modified tRNAs, in proteins translated with selenocysteine, and in the selenium-dependent molybdenum hydroxylases (SDMH). The first two uses both require the selenophosphate synthetase gene, selD. Examining over 500 complete prokaryotic genomes finds selD in exactly two species lacking both the selenocysteine and selenouridine systems, Enterococcus faecalis and Haloarcula marismortui. Surrounding these orphan selD genes, forming bidirectional best hits between species, and detectable by Partial Phylogenetic Profiling vs. selD, are several candidate molybdenum hydroxylase subunits and accessory proteins. We propose that certain accessory proteins, and orphan selD itself, are markers through which new selenium-dependent molybdenum hydroxylases can be found. REVIEWERS: This article was reviewed by Arcady Mushegian and Kira Makarova.